Body composition and physical fitness of different blood groups in Olympic athletes - Ahmed, O. S.; Ahmed, S. S.; Dheyab, R. T. (Journal of Human Sport & Exercise, 2023)
Background and Aim A comprehensive understanding of an athlete's physical fitness and overall condition is paramount in professional sports, especially wrestling. Such insights are instrumental in talent identification, sculpting training regimens, and, ultimately, ensuring success on the field. Given this backdrop, this study embarked on a mission to meticulously investigate the variances in body composition and diverse elements of physical fitness among the elite Olympic athletes of Iraq. The emphasis was on delineating correlations or disparities based on their blood groups.